THE EFFECT OF BOCATION OF COW’S RUMEN CONTENTS ON GROWTH AND HARVEST OF MUSTARD GREENS ON ALLUVIAL SOIL - Normansyah, Hadi Ikhlas; Safwan, Mulyadi; Zulfita, Dwi (Jurnal Sains Mahasiswa Pertanian, 2019)
ABSTRACT             This study aims to determine the effect of giving cow’s rumen contents and looking for the best dose for growth and harvest of mustard greens on alluvial soil. The design used was a Completely Randomized Design (CRD) consisting of five treatments and five repetition, each repetition consist of the three plant samples. The intended treatments is k1 : 400 g/polybag, k2 : 800 g/polybag, k3 : 1200 g/polybag, k4 : 1600 g/polybag and k5 : 2000 g/polybag. The results of the analysis of the diversity by giving various dose of cow’s rumen contents gave no significant effect on almost all variables observed, specifically root volume, total leaf area, dry plant weigh, number of leaves and fresh plant weigh, but significantly affected the number of chlorophyll. This study found no best dosage for cow’s rumen contents for growth and the harvest of mustard greens on alluvial soil but the dosage of cow’s rumen contents which is effective for growth and harvest of mustard green on alluvial soil is indicated by the allocation of cow’s rumen contents at a dose of 400 g/polybag. Keywords : Alluvial, Bocation, Cow’s Rumen, mustard green